« Mon parent, ce nouvel ennemi ». Relations matrimoniales et intériorisation de l’Autre chez les Jebero d’Amazonie péruvienne - Ronan Julou (Journal de la Société des Américanistes, 2009)
Peruvian Amazon, Jebero, kinship, alterity, mythology« My kin, this new enemy ». Matrimonial relations and internalization of the Other among the Jebero of Peruvian Amazon. The Jebero, who stand for the ancient paragon of « Christian Indians » during the colonial period, are facing a deleterious change of their social relationship, marked by the loss of confidence in their close kin, now considered as potential enemies. The Jebero attribute this alteration of their social cohesion to the increase in the number of marriage with outsiders, incarnations of a predatory alterity now internalized. Nevertheless, the author shows that actual tensions aren’t linked to the identity of those outsiders but to the evolution of the relations between affines inside the village him-self. Those mutual accusations and conflicts reveal an underlying transformation of their way to conceive affinity : the affines, usually progressively absorbed by consanguinity, conserve their distances and reveal their otherness. A new conception of affinity that, as suggested by the author in the conclusion, may give sense to the recent claims made by the Jebero to the Peruvian state for the recognition of their native origins and their rights as such.